(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The objective of this paper is to know the operation conditions of the system in terms of power flow, power losses and the weak points of the network. After which, solutions were proposed for solving such problems. The strategic and methodology for planning Criteria are chosen in a way that matches the general standards. A seventeen years plan is considered with short and long term planning applied and computed, system model was designed and a simulation for this model was performed using NEPLAN software. A strategic plan for the 17 year next for 66 kV sub-transmission network has been obtained. The targeted network consists of four rings fed from four 220KV feeding points and capable of providing an expected total demand of 253 MW.